1850 Mass. Gen. Law, ch. 194, §§ 1, 2 as codified in Mass. Gen. Stat., ch. 164 (1873) § 11 - (:unkn) unknown (General Publisher, 1873)
Prohibited manufacturing or selling a slungshot or metallic knuckles. Punishable by fine up to $50 or imprisonment up to 6 months.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS